The benefits and implied costs of JIT sourcing to chinese contractors: A review of literature - Wu, Peng; Pienaar, J.; Feng, Y. (Springer-Verlag Berlin Heidelberg, 2014)
The just-in-time (JIT) concept originates from the Toyota Production System (TPS) and has been adopted in the construction industry for decades to improve logistics and performance. The concept has proven to be effective in reducing inventory level, improving information exchange and supply chain performance. Many new benefits of JIT sourcing have been identified in recent years, such as the improvement in environmental performance for contractors. However, these new benefits are challenged by many academics based on the rigorous criteria that should be followed when applying the JIT sourcing concept. It is therefore necessary to re-evaluate the benefits and costs of JIT sourcing, especially to identify what the implied costs are in order to achieve the benefits. This paper aims to take the first step to re-evaluate JIT sourcing for Chinese contractors for better implementation. According to the research aim, this paper is split into two parts. The first section focuses on explaining the traditional and new benefits of JIT sourcing while the second section aims to investigate the implied costs of these benefits. By knowing the benefits and implied costs, the contractors can be fully prepared to apply JIT sourcing to improve their performance. © 2014 Springer-Verlag Berlin Heidelberg.